Daily Soy–Catfish–Anchovy–Rice (SCAR) Porridge Increases 25(OH)D Serum Levels in Tuberculosis Patients with Vitamin D Receptor Gene Polymorphisms - Dina Keumala Sari; Ridha Dharmajaya; Mutiara Indah Sari; Dewi Masyithah Darlan (The Indonesian Biomedical Journal, 2021)
BACKGROUND: The presence of vitamin D receptor (VDR) polymorphism and high levels of inflammatory markers are predisposing factors indicating disease progression and malnutrition. To meet nutritional needs in maintaining nutritional status in tuberculosis patients with VDR gene polymorphisms (TaqI or FokI), food that is easily absorbed and high in vitamin D, calcium, and protein is needed. This study was conducted to determine whether high vitamin D and calcium porridge called soy–catfish–anchovy–rice (SCAR) porridge would increase 25(OH)D serum levels and other parameters, including calcium, albumin, high-sensivity C-reactive protein (hs-CRP), and blood glucose serum levels.METHODS: The study was a parallel, open, clinical trial. There were 22 subjects in the intervention (I) group who received 50 g of SCAR porridge once per day along with dietary counseling, and 21 subjects in the control (C) group who only received dietary counseling. All subjects with TC and CC (TaqI) or TC and CC (FokI) genotype were included in this study. The intervention lasted for 14 days, and the parameters such as 25(OH)D, calcium, albumin, hs-CRP, and blood glucose serum levels were assessed before and after intervention between groups.RESULTS: All subjects in both groups completed the study. After 14 days of intervention, there was a significant increase in 25(OH)D (p=0.01) and decrease in hs-CRP (p=0.02) serum levels in the I group, and no change was observed in the C group. There was no significant difference in albumin and blood glucose serum levels.CONCLUSION: The results show that 50 g of SCAR porridge per day for 14 days is an effective supplementation that can increase 25(OH)D and decrease hs-CRP serum levels in tuberculosis patients with VDR gene polymorphism.KEYWORDS: vitamin D, hs-CRP, polymorphism, porridge